3x-13+3x-10=12x-6

Simple and best practice solution for 3x-13+3x-10=12x-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x-13+3x-10=12x-6 equation:


Simplifying
3x + -13 + 3x + -10 = 12x + -6

Reorder the terms:
-13 + -10 + 3x + 3x = 12x + -6

Combine like terms: -13 + -10 = -23
-23 + 3x + 3x = 12x + -6

Combine like terms: 3x + 3x = 6x
-23 + 6x = 12x + -6

Reorder the terms:
-23 + 6x = -6 + 12x

Solving
-23 + 6x = -6 + 12x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-12x' to each side of the equation.
-23 + 6x + -12x = -6 + 12x + -12x

Combine like terms: 6x + -12x = -6x
-23 + -6x = -6 + 12x + -12x

Combine like terms: 12x + -12x = 0
-23 + -6x = -6 + 0
-23 + -6x = -6

Add '23' to each side of the equation.
-23 + 23 + -6x = -6 + 23

Combine like terms: -23 + 23 = 0
0 + -6x = -6 + 23
-6x = -6 + 23

Combine like terms: -6 + 23 = 17
-6x = 17

Divide each side by '-6'.
x = -2.833333333

Simplifying
x = -2.833333333

See similar equations:

| 56q^2-19qt-15t^2=0 | | 4(3x-3)=96 | | x*0.7=10 | | 6-5(7m+5)=86 | | 2x+3+x=x+3 | | 18q^2-39qt-189t^2=0 | | 6x-1x=6-6 | | 2i/3i | | 2w+2(1w+283)=19 | | 5p-95p+119p-p=151 | | 3[x+5]=27 | | 8x^2+10x+25= | | 2(3a+1)=5(a-1) | | 66-2r+1=3r-5(r-2) | | F(10.5)= | | 28+x=14 | | 6=x-3/2 | | 2(p+5)-3(p-7)=43 | | (9x^7)(-8x^5)=0 | | 10(d+9)=210 | | 7x-7-5x=2 | | 40-[3c+4]=4[c+5]+c | | 40-[3c+4]=[c+5]+c | | 4m-3=6m+5 | | -7t+4=-10t-14 | | 4[m+4]=40 | | -7+4=-10+-14 | | 2x+50=110 | | 14x^4+92x-42x^2=0 | | 2x-3y+i(x-2y)=4-5i | | -4(7-5m+n)= | | 6+4b=2+5b |

Equations solver categories